Sciences en danger, revues en lutte - Camille Noûs (La Nouvelle Revue du Travail)
The big question today in early 2020 is why more than 150 mainly social science journals are engaged in a vast social movement that erupted last autumn. The answer is simple – because they consider that the French government’s reform plans constitute a clear and present danger to science, education and research, hence to the journals that play an essential role in the scientific knowledge production process. The stakes here are clear. There is a need to denounce the break-up of public services as well as the inevitable exacerbation of social inequality caused by these government reforms (involving, inter alia, pensions, the so-called LPPR multi-annual research programme bill, unemployment benefits, etc.). Relating more specifically to public sector higher education and research, implementing the LPPR plans (a sequel to other neo-liberal reforms from recent years, including pension-related ones) would directly undermine the scientific creation process. This is because the reforms are largely inspired by new public management principles that emphasize outcomes, excellence and performance; quantitative indicators; and managerial rather than scientific or educational perspectives. Their implementation would make academic staff members’ position increasingly precarious while drastically shrinking the resources at their disposal and undermining their scientific output, which should be assessed via peer reviews and not by autocratic ratings or funding agencies. By committing to this movement, the signatory journals are communicating that they do not want to play the management role that is being forced upon them; that they refuse to operate as simple exclusionary machines driven by largely quantitative criteria; and more broadly, that they oppose a process in which science plays second fiddle to management.